The antagonistic activity of certain fungal endophytes against some phytopathogenic fungi through their metabolites and extracellular enzymes - Komeil, Doaa; Saad, Mona (Phytoprotection, 2021)
The objectives of this study were to determine the qualitative production of extracellular enzymes produced by ten endophytic fungi and to investigate their antifungal potential against some phytopathogenic fungi namely, Alternaria alternata, Botrytis cinerea, Fusarium oxysporum and Rhizoctonia solani. In addition, the endophytic fungal isolates were screened for enzyme production by plate assay method. All endophytic fungi were able to produce proteases and cellulases with different levels except Alternaria alternata. Meanwhile, Fusarium, Alternaria, Nigrospora and Phoma species produced amylase. None of the tested endophytic fungi showed laccase production. Endophytic fungi filtrates revealed variable antifungal activities against the tested phytopathogenic fungi with Curvularia lunata filtrate being the most effective. This filtrate induced 48% and 80% growth inhibition of B. cinerea and R. solani, respectively. The phytochemical analysis of the endophytic fungi crude extract disclosed the presence of alkaloids and terpenoids. Morphological observations by optical microscope showed uncommon hyphal deformation and enlargement of cytoplasmic vacuoles of R. solani when treated with C. lunata filtrate. Furthermore, C. lunata (hyphal suspension and filtrate) was examined to control root rot caused by R. solani on faba bean plants in vivo. Both antagonistic treatments significantly reduced root rot severity.